Morphometric and densitometric characteristics of the brainstem locus coeruleus neurons nuclei in rats with experimental arterial hypertension - O. V. Hancheva; M. V. Danukalo; O. V. Melnikova (Zaporozhye State Medical University, 2019)
The aim of our study was to establish the morphodensitometric features of locus coeruleus (LC) neurons nuclei in the brain stem of rats with arterial hypertension of various origin (essential - SHR and endocrine-salt hypertension (ESH)). Matherials and methods: the study was carried out on 30 mature male rats: 10 control Wistar rats, 10 Wistar rats with modeled endocrine-salt AH (ESH) and 10 spontaneously hypertensive rats (SHR) with genetically determined hypertension. The histochemical method of staining with gallocyanine-chrome alum by Einarson was used for the evaluation of morphodensitometric characteristics of the neurons nuclei: the nucleus area, the content and concentration of nucleic acids (NA) in the nucleus. Results: it was found that the highest indices were observed in rats of the SHR line while in rats with ESH the content, RNA concentration and nucleus area decreased. In SHR rats with essential hypertension high synthetic activity was observed in the LC neurons with an increase of the content and concentration of NA. Conclusions. Morphometric and densitometric characteristics of the of the brain stem LC in AH depend on the etiological factor and pathogenesis of hypertension. In essential AH of SHR there is a high synthetic activity in the brainstem LC neurons nuclei along with an increase in the content and concentration of NA. In symptomatic AH in rats with ESH, on the contrary, the structure activity is decreased and characterized by the reduction in nucleus size and NA content in it.